2019
DOI: 10.1093/jac/dkz257
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of colistin alone and in various combinations for the treatment of experimental osteomyelitis due to carbapenemase-producing Klebsiella pneumoniae

Abstract: Objectives In a new experimental model of carbapenemase-producing Klebsiella pneumoniae osteomyelitis we evaluated the efficacy of colistin alone and in various combinations and examined the emergence of colistin-resistant strains and cross-resistance to host defence peptides (HDPs). Methods KPC-99YC is a clinical strain with intermediate susceptibility to meropenem (MIC = 4 mg/L) and full susceptibility to gentamicin, colist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…The combination of meropenem and colistin has been suggested to treat multidrug-resistant K. pneumoniae infections [28]. The results of our time–kill assays showed that monotherapy with colistin may be problematic for the treatment of infections caused by colistin-heteroresistant K. pneumoniae .…”
Section: Discussionmentioning
confidence: 95%
“…The combination of meropenem and colistin has been suggested to treat multidrug-resistant K. pneumoniae infections [28]. The results of our time–kill assays showed that monotherapy with colistin may be problematic for the treatment of infections caused by colistin-heteroresistant K. pneumoniae .…”
Section: Discussionmentioning
confidence: 95%
“…Based on literature data, susceptibility was defined as a MIC ≤ 1 µg/mL for Enterococcus spp. [71]. Rifampin showed synergistic activity in association with FOS against Enterococcus spp., resulting in synergistic effect in 20−100% of cases.…”
Section: Rifampinmentioning
confidence: 93%
“…Synergism rates were not unanimous on all studies but was reported in 23/29 papers. Synergisms rate were 100% in 2 in vitro studies against K. pneumoniae [50,71] and 2 in vivo studies respectively against A. baumannii and E.coli [72,73]. The overall effect was indifferent on most isolates of P. aeruginosa and Enterobacterales.…”
Section: Polymyxinsmentioning
confidence: 95%
“…KPC-99YC is a clinical strain of carbapenemase-producing K. pneumoniae, intermediate to meropenem (MIC, 4 mg/L), and susceptible to colistin (MIC, 1 mg/L) [13,14]. This strain belongs to the epidemic clone ST-258.…”
Section: Bacterial Strainmentioning
confidence: 99%